Sound power level and sound pressure level characterization of a small unmanned aircraft system during flight operations. (May 2017) - Papa, Umberto; Iannace, Gino; Del Core, Giuseppe; Giordano, Giovanna
Unmanned aerial vehicles, actually Federal Aviation Administration calls them unmanned aircraft systems, have aroused a great deal for many applications in the scientific, civil, and military sectors. The goal of this article is to evaluate the acoustic emissions of some small unmanned aircraft systems during normal flight operations (e.g. take off, landing, turning, and hovering) related to electric engines and propellers. This analysis will be useful for developing a system (unmanned aircraft systems Tracking and Reconnaissance System), which will be able to locate a small unmanned aircraft system using its sound power level, in a prefixed area. The investigation on sound power levels and sound pressure level is based on EN ISO 3745, which specifies measurement method. The acoustic measurements were carried out in an anechoic room, and the results of each unmanned aircraft system have been presented and discussed.